Importance of Dietary Changes During the Coronavirus Pandemic: How to Upgrade Your Immune Response - Chaari, Ali; Bendriss, Ghizlane; Zakaria, Dalia; McVeigh, Clare (Frontiers in Public Health, 2020)
The new coronavirus pandemic continues to spread causing further public health, social, and economic issues. The disparities in the rates of death between countries poses questions about the importance of lifestyle habits and the immune status of populations. An exploration of dietary habits and COVID-19-related death might unravel associations between these two variables. Indeed, while both nutritional excess and deficiency are associated with immunodeficiency, adequate nutrition leading to an optimally functioning immune system may be associated with better outcomes with regards to preventing infection and complications of COVID-19, as well as developing a better immune response to other pathogenic viruses and microorganisms. This article outlines the key functions of the immune system and how macronutrients, micronutrients, and metabolites from the gut microbiome can be essential in the development of an efficient immune system. In addition, the effects of intermittent fasting on the inflammatory state as well as metabolic parameters will be discussed.